(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate the degree of conversion (DC) and cohesive strength (CS) of two conventional resin cements and a self-adhesive resin cement using different forms of activation. Two conventional dual resin cements (Variolink II and RelyX ARC) and a self-adhesive resin cement were polymerized in three different ways of activation, namely Chemically Activated (CA), Light Activated with Interposition of a resin disc (LI) and Light-Activated (L). The DC was evaluated using Fourier Transformed Infrared Spectroscopy - FTIR (Spectrum 100). In the CS test, the samples were tested until fracture in a universal testing machine (Instron 4411). The mean values obtained in the DC and CS tests were evaluated using two-way analysis of variance (ANOVA) (cement and activation) and Tukey test (p≤0.05). Irrespective of the activation mode, RelyX ARC showed the highest DC values, RelyX U200, the lowest values, and Variolink II intermediate values. Group L always had higher for DC and CS values than group CA. Among the resin cements, irrespective of the activation mode, there were no differences in CS values. The chemical activation mode of dual resin cements led to lower DC and CS values. RelyX ARC cement had the highest DC values and RelyX U200 cement the lowest values, however, in relation to CS, there were no differences.